(untitled) (ENTHYMEMA, 2020)
The essay focuses on G., the eponymous hero of John Berger’s neo-modernist novel, and on some minor characters in the story – i.e., the women figures and the stone guest – in order to clarify Berger’s re-interpretation of the Don Juan archetype as a biological and “anti-historical” revolutionist. Special attention is paid to the narrative modalities through which characters are constructed in a novel that brings together both realist and modernist features, in order to criticize the political disengagement of postmodernist relativism.